Sholat Dhuha May Reduce The Risk of Knee Osteoarthritis in The Elderly: Preliminary Research - Elman Boy; Des Suryani; Debby Mirani Lubis; Balemun Kaisar Harahap (Buletin Farmatera, 2022)
Abstract: Osteoarthritis is one of the most common degenerative diseases that attack the joints and cause deformity in the elderly. The purpose of this study was to investigate the link between dhuha prayer and the risk of knee osteoarthritis (kOA). Methods: cross-sectional and purposive sampling, with inclusion criteria including Muslim women cured in the Government Binjai Senior Care, age greater than or equal to 60 years, communicative, signing informed consent, and providing complete answers to the WOMAC questionnaire to assess kOA risk. The interview form was used to count the number of rak'ahs of dhuha prayer that are usually performed every day. SPSS was used to analyze the data, and the Spearman Rank test was used. The research criteria were met by 30 of 101 prospective respondents. The respondents ages range from 60 to 85 years old, 68% are at risk of mild kOA, and there is a link between the number of rak'ahs of dhuha prayer and a lower risk of kOA. Conclusion: The more rak'ahs of dhuha prayer that are performed on a daily basis, the lower the risk of KOA.